Physical Fitness and Energy Metabolism of the Elderly - Shinkai, Shoji; Watanabe, Tsutomu; Watanabe, Shuichiro (Nihon Rōnen Igakkai zasshi, 1993)
It is generally accepted that decreased lean body mass (LBM) with aging is responsible for decline in basal metabolism (BMR) of the elderly. However, multiple regression analysis of BMR and related factors for middle- to older-aged subjects showed that decline in BMR with aging could not be explained only by decrease in LBM. Basal heat production rates per essential body mass (EBM) and per fat tissue mass (FTM) by sex and by age class were estimated using the regression analysis proposed by Chirifu. It was found that the basal heat production per EBM decreased with aging, indicating that both decreases in active tissue mass and BMR per unit of active tissue mass were involved in reduced BMR for the elderly. A 15-week aerobic exercise training course prescribed for mildly obese middle- to older-aged women improved their fitness level and body composition, i.e., decrease in FTM with increase in EBM. The basal heat production rate per EBM increased by 21%. These results suggest that aerobic exercise training is effective for improving the metabolism of active tissue in the middle-aged and the elderly. Although there was a wide inter-individual variation in BMR in the elderly over 70 years of age, the BMR tended to increase depending on the level of daily activity. In conclusion, physical exercise and an active daily life are important for decelerating the decrease in BMR for the elderly through maintaining active tissue mass and its basal metabolism